URGENSI ŚLOKA DAN MANTRA BERBAHASA SANSKERTA BAGI PENDHARMA WACANA - Wayan Ayumita Astrina; Ida Kade Suparta (IAHN Gde Pudja Mataram, 2022)
Persuasion efforts in order to increase the śraddhā and devotion (bhakti) of Hindus people can be done through the application of the dharma wacana method with a variety of topics which include the teachings of susīla, tattwa, upacāra, and traditions. Pendharma wacana (speaker) usually inserts holy verses (śloka) and mantras in Sanskrit in the material presented, so that it indirectly raises the general perception that verse and mantra quotes are one of the distinctive elements of a dharma wacana. Sanskrit śloka and mantras are considered to have a very significant position in every dharma wacana activity, but no one has done an in-depth study of it. Article purpose is urgency of śloka and mantra in Sanskrit for the dharma wacana. Qualitative research procedures were applied to obtain a clear description related to the purpose of quoting śloka and mantra in Sanskrit in conveying dharma wacana, as well as the implications for the pendharma wacana and the audience. This research results that both śloka and mantras in Sanskrit have a rhetorical function and can be used as an effort to attract the attention of the audience. The rhetorical function is shown from the pendharma wacana using śloka and mantra in Sanskrit as justification for the truth of the material presented to persuade the audience. In relation to efforts to attract the attention of the audience, there are two things that need to be considered, śloka and mantra must be sung in a certain style and have relevance to the needs of the audience.